2015
DOI: 10.1038/icb.2015.39
|View full text |Cite
|
Sign up to set email alerts
|

IRF5: a rheostat for tumor‐infiltrating lymphocyte trafficking in breast cancer?

Abstract: Breast cancer (BC) development and progression is influenced by the intrinsic properties of tumor cells as well as their surrounding microenvironment. Cells found in the microenvironment include stroma cells, fibroblasts, endothelial cells, pericytes, adipocytes and various types of infiltrating immune cells. The immune infiltrate generally includes myeloid cells and lymphocytes (tumor infiltrating lymphocytes (TILs)) composed of B cells, T cells and natural killer cells. Recently, the immune response has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…IRF5 is a marker of M1 macrophages and plays the role of regulating tumor infiltration (57). Previous studies showed that IRF5 changed the immune microenvironment of tumors by regulating the expression of pro-inflammatory and anti-inflammatory cytokines/chemokines in breast cancer (58,59). Our studies observed that an increase in SIRT7 expression was correlated with the M1 macrophage marker IRT5.…”
Section: Discussionsupporting
confidence: 64%
“…IRF5 is a marker of M1 macrophages and plays the role of regulating tumor infiltration (57). Previous studies showed that IRF5 changed the immune microenvironment of tumors by regulating the expression of pro-inflammatory and anti-inflammatory cytokines/chemokines in breast cancer (58,59). Our studies observed that an increase in SIRT7 expression was correlated with the M1 macrophage marker IRT5.…”
Section: Discussionsupporting
confidence: 64%
“…ChIP assays were performed with the EZ-Magna ChipTM A kit (Millipore) according to the manufacturer's instructions. A total of 1×10 7 Hela cells were fixed in 1% formaldehyde at room temperature for 10 min. The cell lysates were sonicated to generate 200-1,000 bp DNA fragments.…”
Section: Chromatin Immunoprecipitation (Chip) Assaymentioning
confidence: 99%
“…4 It is reported that the expression of IRF5 is reduced in gastric cancer, renal cancer, and is associated with the progression and metastasis of breast cancer. [5][6][7] Massimino M suggested that IRF5 is a target of BCR-ABL kinase activity and reduces CML cell proliferation. 8,9 Cevik O reported that IRF5 inhibits hepatitis C virus (HCV) replication and HCV-associated hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…5B) is regulated by either S176A or S165A. This gene is considered to be a novel regulator of C-X-C motif chemokine ligand 13 (CXCL13) expression in cancer (18). In contrast, MYCL1 (Fig.…”
Section: Figure 3 Phosphorylation Of Ser-176 Differentially Regulatementioning
confidence: 99%